5.3.4 Problems 301 to 400

Table 5.291: Second order ode

#

ODE

Mathematica

Maple

910

\[ {}x^{\prime \prime }+100 x = 225 \cos \left (5 t \right )+300 \sin \left (5 t \right ) \]

911

\[ {}x^{\prime \prime }+25 x = 90 \cos \left (4 t \right ) \]

912

\[ {}m x^{\prime \prime }+k x = F_{0} \cos \left (\omega t \right ) \]

913

\[ {}x^{\prime \prime }+4 x^{\prime }+4 x = 10 \cos \left (3 t \right ) \]

914

\[ {}x^{\prime \prime }+3 x^{\prime }+5 x = -4 \cos \left (5 t \right ) \]

915

\[ {}2 x^{\prime \prime }+2 x^{\prime }+x = 3 \sin \left (10 t \right ) \]

916

\[ {}x^{\prime \prime }+3 x^{\prime }+3 x = 8 \cos \left (10 t \right )+6 \sin \left (10 t \right ) \]

917

\[ {}x^{\prime \prime }+4 x^{\prime }+5 x = 10 \cos \left (3 t \right ) \]

918

\[ {}x^{\prime \prime }+6 x^{\prime }+13 x = 10 \sin \left (5 t \right ) \]

919

\[ {}x^{\prime \prime }+6 x^{\prime }+13 x = 10 \sin \left (5 t \right ) \]

920

\[ {}x^{\prime \prime }+2 x^{\prime }+26 x = 600 \cos \left (10 t \right ) \]

921

\[ {}x^{\prime \prime }+8 x^{\prime }+25 x = 200 \cos \left (t \right )+520 \sin \left (t \right ) \]

928

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }-9 y = 0 \]

929

\[ {}4 y^{\prime \prime }-4 y^{\prime }+y = 0 \]

930

\[ {}x^{2} y^{\prime \prime }-x \left (x +2\right ) y^{\prime }+\left (x +2\right ) y = 0 \]

931

\[ {}\left (1+x \right ) y^{\prime \prime }-\left (x +2\right ) y^{\prime }+y = 0 \]

932

\[ {}\left (-x^{2}+1\right ) y^{\prime \prime }+2 x y^{\prime }-2 y = 0 \]

933

\[ {}\left (-x^{2}+1\right ) y^{\prime \prime }-2 x y^{\prime }+2 y = 0 \]

934

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-\frac {1}{4}\right ) y = 0 \]

1249

\[ {}y^{\prime \prime }+2 y^{\prime }-3 y = 0 \]

1250

\[ {}y^{\prime \prime }+3 y^{\prime }+2 y = 0 \]

1251

\[ {}6 y^{\prime \prime }-y^{\prime }-y = 0 \]

1252

\[ {}2 y^{\prime \prime }-3 y^{\prime }+y = 0 \]

1253

\[ {}y^{\prime \prime }+5 y^{\prime } = 0 \]

1254

\[ {}4 y^{\prime \prime }-9 y = 0 \]

1255

\[ {}y^{\prime \prime }-9 y^{\prime }+9 y = 0 \]

1256

\[ {}y^{\prime \prime }-2 y^{\prime }-2 y = 0 \]

1257

\[ {}y^{\prime \prime }+y^{\prime }-2 y = 0 \]

1258

\[ {}y^{\prime \prime }+4 y^{\prime }+3 y = 0 \]

1259

\[ {}6 y^{\prime \prime }-5 y^{\prime }+y = 0 \]

1260

\[ {}y^{\prime \prime }+3 y^{\prime } = 0 \]

1261

\[ {}y^{\prime \prime }+5 y^{\prime }+3 y = 0 \]

1262

\[ {}2 y^{\prime \prime }+y^{\prime }-4 y = 0 \]

1263

\[ {}y^{\prime \prime }+8 y^{\prime }-9 y = 0 \]

1264

\[ {}4 y^{\prime \prime }-y = 0 \]

1265

\[ {}y^{\prime \prime }-y = 0 \]

1266

\[ {}2 y^{\prime \prime }-3 y^{\prime }+y = 0 \]

1267

\[ {}y^{\prime \prime }-y^{\prime }-2 y = 0 \]

1268

\[ {}4 y^{\prime \prime }-y = 0 \]

1269

\[ {}y^{\prime \prime }-\left (2 \alpha -1\right ) y^{\prime }+\alpha \left (\alpha -1\right ) y = 0 \]

1270

\[ {}y^{\prime \prime }+\left (3-\alpha \right ) y^{\prime }-2 \left (\alpha -1\right ) y = 0 \]

1271

\[ {}2 y^{\prime \prime }+3 y^{\prime }-2 y = 0 \]

1272

\[ {}y^{\prime \prime }+5 y^{\prime }+6 y = 0 \]

1273

\[ {}y^{\prime \prime }-2 y^{\prime }+2 y = 0 \]

1274

\[ {}y^{\prime \prime }-2 y^{\prime }+6 y = 0 \]

1275

\[ {}y^{\prime \prime }+2 y^{\prime }-8 y = 0 \]

1276

\[ {}y^{\prime \prime }+2 y^{\prime }+2 y = 0 \]

1277

\[ {}y^{\prime \prime }+6 y^{\prime }+13 y = 0 \]

1278

\[ {}4 y^{\prime \prime }+9 y = 0 \]

1279

\[ {}y^{\prime \prime }+2 y^{\prime }+\frac {5 y}{4} = 0 \]

1280

\[ {}9 y^{\prime \prime }+9 y^{\prime }-4 y = 0 \]

1281

\[ {}y^{\prime \prime }+y^{\prime }+\frac {5 y}{4} = 0 \]

1282

\[ {}y^{\prime \prime }+4 y^{\prime }+\frac {25 y}{4} = 0 \]

1283

\[ {}y^{\prime \prime }+4 y = 0 \]

1284

\[ {}y^{\prime \prime }+4 y^{\prime }+5 y = 0 \]

1285

\[ {}y^{\prime \prime }-2 y^{\prime }+5 y = 0 \]

1286

\[ {}y^{\prime \prime }+y = 0 \]

1287

\[ {}y^{\prime \prime }+y^{\prime }+\frac {5 y}{4} = 0 \]

1288

\[ {}y^{\prime \prime }+2 y^{\prime }+2 y = 0 \]

1289

\[ {}u^{\prime \prime }-u^{\prime }+2 u = 0 \]

1290

\[ {}5 u^{\prime \prime }+2 u^{\prime }+7 u = 0 \]

1291

\[ {}y^{\prime \prime }+2 y^{\prime }+6 y = 0 \]

1292

\[ {}y^{\prime \prime }+2 a y^{\prime }+\left (a^{2}+1\right ) y = 0 \]

1293

\[ {}t^{2} y^{\prime \prime }+t y^{\prime }+y = 0 \]

1294

\[ {}t^{2} y^{\prime \prime }+4 t y^{\prime }+2 y = 0 \]

1295

\[ {}t^{2} y^{\prime \prime }+3 t y^{\prime }+\frac {5 y}{4} = 0 \]

1296

\[ {}t^{2} y^{\prime \prime }-4 t y^{\prime }-6 y = 0 \]

1297

\[ {}t^{2} y^{\prime \prime }-4 t y^{\prime }+6 y = 0 \]

1298

\[ {}t^{2} y^{\prime \prime }-t y^{\prime }+5 y = 0 \]

1299

\[ {}t^{2} y^{\prime \prime }+3 t y^{\prime }-3 y = 0 \]

1300

\[ {}t^{2} y^{\prime \prime }+7 t y^{\prime }+10 y = 0 \]

1301

\[ {}y^{\prime \prime }+t y^{\prime }+{\mathrm e}^{-t^{2}} y = 0 \]

1302

\[ {}t y^{\prime \prime }+\left (t^{2}-1\right ) y^{\prime }+t^{3} y = 0 \]

1303

\[ {}y^{\prime \prime }-2 y^{\prime }+y = 0 \]

1304

\[ {}9 y^{\prime \prime }+6 y^{\prime }+y = 0 \]

1305

\[ {}4 y^{\prime \prime }-4 y^{\prime }-3 y = 0 \]

1306

\[ {}4 y^{\prime \prime }+12 y^{\prime }+9 y = 0 \]

1307

\[ {}y^{\prime \prime }-2 y^{\prime }+10 y = 0 \]

1308

\[ {}y^{\prime \prime }-6 y^{\prime }+9 y = 0 \]

1309

\[ {}4 y^{\prime \prime }+17 y^{\prime }+4 y = 0 \]

1310

\[ {}16 y^{\prime \prime }+24 y^{\prime }+9 y = 0 \]

1311

\[ {}25 y^{\prime \prime }-20 y^{\prime }+4 y = 0 \]

1312

\[ {}2 y^{\prime \prime }+2 y^{\prime }+y = 0 \]

1313

\[ {}9 y^{\prime \prime }-12 y^{\prime }+4 y = 0 \]

1314

\[ {}y^{\prime \prime }-6 y^{\prime }+9 y = 0 \]

1315

\[ {}9 y^{\prime \prime }+6 y^{\prime }+82 y = 0 \]

1316

\[ {}y^{\prime \prime }+4 y^{\prime }+4 y = 0 \]

1317

\[ {}4 y^{\prime \prime }+12 y^{\prime }+9 y = 0 \]

1318

\[ {}y^{\prime \prime }-y^{\prime }+\frac {y}{4} = 0 \]

1319

\[ {}t^{2} y^{\prime \prime }-4 t y^{\prime }+6 y = 0 \]

1320

\[ {}t^{2} y^{\prime \prime }+2 t y^{\prime }-2 y = 0 \]

1321

\[ {}t^{2} y^{\prime \prime }+3 t y^{\prime }+y = 0 \]

1322

\[ {}t^{2} y^{\prime \prime }-t \left (2+t \right ) y^{\prime }+\left (2+t \right ) y = 0 \]

1323

\[ {}x y^{\prime \prime }-y^{\prime }+4 x^{3} y = 0 \]

1324

\[ {}\left (x -1\right ) y^{\prime \prime }-x y^{\prime }+y = 0 \]

1325

\[ {}x^{2} y^{\prime \prime }-\left (x -\frac {3}{16}\right ) y = 0 \]

1326

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-\frac {1}{4}\right ) y = 0 \]

1327

\[ {}t^{2} y^{\prime \prime }-3 t y^{\prime }+4 y = 0 \]

1328

\[ {}t^{2} y^{\prime \prime }+2 t y^{\prime }+\frac {y}{4} = 0 \]

1329

\[ {}2 t^{2} y^{\prime \prime }-5 t y^{\prime }+5 y = 0 \]